The role of youth programmes in the transition from school to work - Lena Schröder (Institute for Labour Market Policy Evaluation (IFAU), 2004)
The purpose of the study is to investigate how labour market regulation, modified by educational systems, affects the magnitude, composition and targeting of Youth Programmes. The data used include Ireland, France, the Netherlands, Scotland and Sweden. Although not fully comparable, the data provide detailed information on Youth Programmes that can not be found in other larger comparative data sets. Based on the combination of the strictness of labour market regulation and the linkages from education to the labour market the countries are classified into three transition regimes. The first tentative result is that the propensity to intervene in the transition from school to work is strongest in countries with strict labour market regulation in combination with weak linkages from the educational system to the labour market. In these countries the targeting of the large-scale programmes seems to be very broad. Other tentative results are that Youth Programmes providing only work experience are used as a measure to compensate for strict labour market regulation, while weak linkages from education to the labour market seems to evoke the need for Programmes providing certified occupational training. The results thus suggest that Youth Programmes play different roles in different countries, and that conclusions regarding the relative effectiveness of programmes can not be transferred from one country to another, without paying attention to the degree of labour market regulation and the special features of the educational systems. Another implication is that it might be considered whether educational and/or labour market reforms could be an alternative to some of the programmes, especially in countries with extensive use of Youth Programmes.
Keywords: J40; 330; Youth programmes; labour market; education